Enhancing students' critical thinking skills through engagement with innovative pedagogical practices in Global South. Issue 4 (7th June 2022) - Okolie, Ugochukwu Chinonso; Igwe, Paul Agu; Mong, Ifeanyi Kalu; Nwosu, Hyginus Emeka; Kanu, Clementina; Ojemuyide, Chidiebere C.
ABSTRACT: This study shows how HE teachers (particularly, business management and vocational studies) experience the teaching of critical thinking to foster student development of critical thinking skills (CTS) while working across diverse international contexts. Using a qualitative online survey and interview methodologies, we obtained rich information from 55 participants from 26 countries in the Global South including HE teachers who incorporate CTS into their teaching practices and those who had studied and briefly taught in developed countries' universities where CT is embedded into the HE learning with an understanding of the subject under study. Focusing on three dominant themes from the thematic analysis, we analyze three key approaches that HE teachers can adopt to enhance students' development of CTS which include: teaching strategies, active learning, setting problem or inquiry. Also, we discuss the perceived challenges that HE teachers may experience in the course of promoting teaching for CTS.